A Cloud-Based Container Microservices: A Review on Load-Balancing and Auto-Scaling Issues - Rabiu, Shamsuddeen; Huah Yong, Chan; Mashita Syed Mohamad, Sharifah (International Journal of Data Science, 2022)
Microservices are being used by businesses to split monolithic software into a set of small services whose instances run independently in containers. Load balancing and auto-scaling are important cloud features for cloud-based container microservices because they control the number of resources available. The current issues concerning load balancing and auto-scaling techniques in Cloud-based container microservices were investigated in this paper. Server overloaded, service failure and traffic spikes were the key challenges faced during the microservices communication phase, making it difficult to provide better Quality of Service (QoS) to users. The aim is to critically investigate the addressed issues related to Load balancing and Auto-scaling in Cloud-based Container Microservices (CBCM) in order to enhance performance for better QoS to the users.